Analisis Faktor-Faktor Penyebab Rendahnya Minat Baca Siswa di MA Al-Furqon - Miftah Nurul Ma’arif; Euis Hayun Toyibah; Putri Ribcha Azzahra; Indri Ramdani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This research aims to evaluate the factors that cause students' low interest in reading at MA Al-Furqon. Descriptive qualitative data collection methods were used, and data collection was carried out through documentation, interviews and observations. This research also uses various references from various articles, journals and other websites. Data shows that MA Al-Furqon students' interest in reading is still low. Two factors were found. Internal factors are the lack of students' reading habits caused by students' interest in reading. And external factors include the school environment, libraries, books and reading materials, family, and the influence of technology and television.